NOMINA PENGACU PERSONA KETIGA DALAM DALAM MASYARAKAT TUTUR BERBAHASA JAWA - Basuki Basuki; Umi Hartati (Universitas Sarjanawiyata Tamansiswa, 2016)
The objectives of this research are to describe (1) the basic of the use of third person in the Javanese speech community (2) the function of the third person noun in the Javanese speech community (3) the meaning of thirs person noun in the Javanese speech community ). To achieve the objectives, the sociolinguistics approach is used for this research. This research is taking place in Surakarta through the qualitative method by using comparative functional and contextual technique analysis. The result of the research shows that (1) the use of the third person nominated is age, sex, attitude of the speaker, family relation, or profession, (2) the function of third person nomina is to express the difference of age, sex, attitude of the speaker, family relation, or profession age, (3) the meaning of the third person nomina in Javanese speech community is to soften, neutralize, and harsh the meaning.